Monocytoid B cell lymphoma. Issue 1 (January 1991) - Banerjee, S S; Harris, M; Eyden, B P; Radford, J A; Harrison, C J; Mainwaring, A R
Abstract : The clinical, light microscopic, ultrastructural, immunocytochemical and cytogenetic features of a case of monocytoid B cell lymphoma were investigated. The tumour initially affected the cervical and supraclavicular nodes, but 33 months later affected the left parotid salivary gland. The patient had subclinical Sjögren's syndrome. The neoplastic cells showed characteristic morphological features and had peri- and interfollicular distribution in the node. Immunocytochemically the tumour cells were L26, 4KB5, MB2, CD19, CD20, CD22 and IgM/kappa positive. Prominent plasmablastic plasmacytoid differentiation was present in the recurrent tumour, suggesting an origin from post-follicular B cells. The lymphoma cells showed unusual cytogenetic abnormalities.